2003
DOI: 10.1093/emboj/cdg004
|View full text |Cite
|
Sign up to set email alerts
|

RelB is required for Peyer's patch development: differential regulation of p52-RelB by lymphotoxin and TNF

Abstract: Targeted disruption of the Rel/NF‐κB family members NF‐κB2, encoding p100/p52, and RelB in mice results in anatomical defects of secondary lymphoid tissues. Here, we report that development of Peyer's patch (PP)‐organizing centers is impaired in both NF‐κB2‐ and RelB‐deficient animals. IL‐7‐induced expression of lymphotoxin (LT) in intestinal cells, a crucial step in PP development, is not impaired in RelB‐deficient embryos. LTβ receptor (LTβR)‐deficient mice also lack PPs, and we demonstrate that LTβR signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
195
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(207 citation statements)
references
References 63 publications
10
195
1
1
Order By: Relevance
“…Mice with a point mutation in nik (aly/aly mice) lack multiple secondary lymphoid organs (Miyawaki et al, 1994;Koike et al, 1996;Shinkura et al, 1999) and share several phenotypic similarities with lymphotoxin and IKKa single knockout animals (Mebius, 2003;Bonizzi and Karin, 2004). p52/RelB, which is activated downstream of NIK and IKKa, is thought to be the primary transcriptional mediator of several key organogenic factors including CXCL12, CXCL13, CCL19, CCL21 and MadCAM-1 (Yilmaz et al, 2003). The p52 single knockout lacks normal B-cell follicles, germinal centers (GCs) and Peyer's patch development (Caamano et al, 1998;Franzoso et al, 1998;Paxian et al, 2002); RelB is likewise also required for Peyer's patch development (Yilmaz et al, 2003).…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with a point mutation in nik (aly/aly mice) lack multiple secondary lymphoid organs (Miyawaki et al, 1994;Koike et al, 1996;Shinkura et al, 1999) and share several phenotypic similarities with lymphotoxin and IKKa single knockout animals (Mebius, 2003;Bonizzi and Karin, 2004). p52/RelB, which is activated downstream of NIK and IKKa, is thought to be the primary transcriptional mediator of several key organogenic factors including CXCL12, CXCL13, CCL19, CCL21 and MadCAM-1 (Yilmaz et al, 2003). The p52 single knockout lacks normal B-cell follicles, germinal centers (GCs) and Peyer's patch development (Caamano et al, 1998;Franzoso et al, 1998;Paxian et al, 2002); RelB is likewise also required for Peyer's patch development (Yilmaz et al, 2003).…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
“…p52/RelB, which is activated downstream of NIK and IKKa, is thought to be the primary transcriptional mediator of several key organogenic factors including CXCL12, CXCL13, CCL19, CCL21 and MadCAM-1 (Yilmaz et al, 2003). The p52 single knockout lacks normal B-cell follicles, germinal centers (GCs) and Peyer's patch development (Caamano et al, 1998;Franzoso et al, 1998;Paxian et al, 2002); RelB is likewise also required for Peyer's patch development (Yilmaz et al, 2003). Although LN development occurs in RelB knockout mice, the nodes are small at birth and are resorbed perinatally.…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%
“…Indeed, genetic analysis indicated that RelB plays an essential role in lymph node development, especially in maintaining lymph node architecture in adult mice (Weih et al, 2001;Yilmaz et al, 2003). Important lymphoid chemokine genes, such as BLC and SLC, were shown to be RelB target genes (Basak et al, 2008;Schneider et al, 2004) via a proposed variant kappaB site that recruits RelB-but not RelA-containing dimers upon LTβR stimulation (Bonizzi et al, 2004).…”
Section: Non-canonical Activation Of Nf-κb/relb Dna Binding Acitvitymentioning
confidence: 99%
“…1b). Although NIK stabilization is required for receptor-induced processing of p100 and activation of RelBp52 (refs 25,26), some basal processing of p100 and nuclear translocation of RelB-p52 does occur under resting conditions in the absence of visible NIK levels as well as in the absence of functional NIK 25,28 . Moreover, basal cytoplasmic-nuclear shuttling of NF-kB family members has been reported to contribute to the basal transcriptional regulation of target genes by NF-kB 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Stabilization of NIK leads to constitutive processing of p100 to p52 and activation of the alternative RelB-p52 pathway 25,26 . While NIK was found to be dispensable for the activation of IKKb-dependent classical pathway 27,28 , in MM, NIK stabilization was shown to activate the classical pathway presumably due to direct interaction between NIK and IKKb 23 . Surprisingly, RNAimediated silencing of IKKa, the kinase through which NIK activates the alternative NF-kB pathway 8,29 did not influence the survival of MM cells 23 , whereas pharmacological inhibition of IKKb in MM cells harbouring NIK stabilizing mutations led to apoptosis 23 .…”
mentioning
confidence: 96%